Awareness in reducing single-use plastic: A case study of students in UKM - Mohd Nasir , Muhammad Amir Sahmat, Hanim Kamaruddin , Farrah Illanie Razman , Auni Wafiqah; Muhammad Wajih Zakwan Hanif, Nadzirah Romzi , Nursyahirah Faizal, (Opción)
PlasThis paper seeks a review on awareness and practicing habits of businesses and students in UKM in the effort to reduce single-use plastic usage. Primary data were obtained through a questionnaire survey of randomly sampled 100 students, business owners and staff in UKM. Results of the survey showed a good awareness level amongst the respondents with regard to single use of plastic in UKM campus. The conclusion of this survey is that the general demographic in UKM is willing to opt for more environmentally friendly products to replace heavy use of plastics and accepting of reducing single use plastic policies